Promoter-Dependent Translation Controlled by p54(nrb) and hnRNPM during Myoblast Differentiation - Ainaoui, Nadera (PLoS One, 2015)
Fibroblast growth factor 1 (FGF1) is induced during myoblast differentiation at both transcriptional and translational levels. Here, we identify hnRNPM and p54(nrb)/NONO present in protein complexes bound to the FGF1 promoter and to the mRNA internal ribosome entry site (IRES). Knockdown or overexpression of these proteins indicate that they cooperate in activating IRES-dependent translation during myoblast differentiation, in a promoter-dependent manner. Importantly, mRNA transfection and promoter deletion experiments clearly demonstrate the impact of the FGF1 promoter on the activation of IRES-dependent translation via p54(nrb) and hnRNPM. Accordingly, knockdown of either p54 or hnRNPM also blocks endogenous FGF1 induction and myotube formation, demonstrating the physiological relevance of this mechanism and the role of these two proteins in myogenesis. Our study demonstrates the cooperative function of hnRNPM and p54(nrb) as regulators of IRES-dependent translation and indicates the involvement of a promoter-dependent mechanism.